Agama dan Etos Bisnis Elit Pesantren Salafiyah - Djakfar, Muhammad (Akutansi Bisnis & Manajemen ( ABM ), 2007)
This study intended to understand deeper the relationship between religion and business ethics of the elites in pondok pesantren salafiyah among the nahdliyin, which so far has not been frequently researched, that took place in pondok pesantren Assirojiyah Sampang, Madura. In accordance with that purpose, the present study used a qualitative approach, employing a phenomenology method. By using participatory observation technique, in-depth interview, and documentary study, the collected data of the study were then described in regard to the believed religious practices. In addition to that, those were also data related to reasons and motives that drove the elite to perform business activities, and how those practices were implemented in their daily activities. The result of the study showed that pesantren Assirojiyah is one of the nahdliyin community which implemented the practice of the teachings in ahlus sunnah wal jamaah. Business was performed as normatively, the Qur’an and Sunnah teach that moslems are to work hard, so that they will be economically independent, and have great capital in struggling for the Islamic Syareat. Therefore, business should be done professionally, as the Prophet professionally did.